Blurred territory: Aestheticization of urban and regional data visualization cheat sheets (REVISTA NODO, 2022)
Design research results about the academic use of data visualization cheat sheets in urban and regional studies (iaur, in Spanish). It presents a quantitative and qualitative analysis of forty-one (41) undergraduate architecture degree thesis published in 2021. A correlation matrix is developed for evaluating data. It depicts that iaur are not being used as a diagnostic tool to define urban intervention places. The working hypothesis is that iaur have lost its communication capability due to its insertion in the image-consumption economy that characterizes contemporary post capitalist society. To push forward the findings, two deliberately artistic iaur are proposed. Lipovetsky & Serroy’s concept of aestheticization is used as theoretical reference. The article argues that such aestheticization of graphic representation methods in architecture is part of a larger process of aestheticization involving the classroom and the city as a whole. The purpose of the debate is to wonder if the passage from traditional drawings to aestheticized urban cheat sheets comes along with urban informality social problems to be left unattended, which would derive in the opposite outcome: blurring the territory.
Keywords: qualitative analysis; quantitative analysis; digital art; urban design; infographics